European Marine Observation and Data Network EMODnet Physics - Novellino, Antonio; D'Angelo, Paolo (GEOmedia, 2014)
Recently the European Commission undertook steps towards a European Marine Observation and Data Network (EMODnet) in order to standardize method for observing and assessing the grade of the Member States seas and improve access to high quality data. Since 2008-2009, European Commission, represented by the Directorate-General for Maritime Affairs and Fisheries (DG MARE), is running several service contracts for creating pilot thematic components of the ur-EMODNET: Biology, Bathymetry, Chemistry, Geology, Habitats, and Physics. The existing EMODnet-Physics portal (www.emodnet-physics.eu) is based on a strong collaboration between EuroGOOS member institutes and its regional operational oceanographic systems (ROOSs), and the National Oceanographic Data Centres (NODCs), and it is a marine observation information system. It includes systems for physical data from the whole Europe (wave height and period, temperature of the water column, wind speed and direction, salinity of the water column, horizontal velocity of the water column, light attenuation, and sea level) provided mainly by fixed stations and ferry-box platforms, discovering related data sets (both near real time and historical data sets), viewing and downloading of the data from about 2100 platforms (www.emodnetphysics.eu/map) and thus contributing towards the definition of an operational European Marine Observation and Data Network (EMODnet).